PENERAPAN MODEL E-LEARNING BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR MAHASISWA PADA MATAKULIAH AN-ORGANIK II - Elva Yasmi; Ervi Yenni; Sri Wilda Albeta (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2017)
This study was conducted in an effort to improve learning outcomes and learning motivation. The population in this study were students of Chemistry Education, University of Riau. The Samples of this research is fifth semester students. Class experiments using problem-based e-learning model, while the control class using classical learning. To test research hypothesis on difference learning motivation and improved learning outcomes using independent sample T-test SPSS-20. To Test research hypothesis on Correlations between students motivation in learning and learning outcomes using Correlations SPSS-20. The result showed that : 1) there was a significant difference in motivation and learning outcomes of students who are taught using a problem-based e-learning model, than students who are taught using classical learning; 2) there was no correlation learning motivation and learning outcomes of students who are taught by classical learning; 3) there was correlation between motivation to learn the results of student learning is taught by Problem-Based E-Learning Model.